Constraints in Availing the Livestock Extension Services under state Department of Animal Husbandry as perceived by women Livestock Farmers - Jyoti Yadav , Hema Tripathi , B. L. Balaraju and Rekha Yadav, (Indian Journal of Extension Education, 2017)
Livestock sector is one of the most important sources of livelihood in rural domain and livestock farming is mainly underthe control of rural women at household level. But unfortunately, they have least access to livestock extension services.There are many constraints which are being faced by women livestock farmers in availing the livestock extensionservices. To explore these constraints, the current research was done in four districts of central plain zone of Uttar Pradesh.A multi-stage random sampling technique was employed for the selection of women livestock farmers. Data werecollected from randomly selected 200 women livestock farmers from 8 villages. Lack of training related to scientificlivestock rearing was ranked first in the constraints perceived by women livestock farmers in availing the livestockextension services followed by lack of awareness on government livestock extension programmes/schemes (rank II) andlack of time to attend livestock extension meeting, goshties, camp etc. (rank III).